Product and Service Quality Improvement in Manufacturing: a Study of Optical Lens Manufacturing in Indonesia - Refli Simbolon; Sugeng Santoso (Media Ekonomi dan Manajemen, 2021)
For optical lens manufacturing the development of product and service quality is a key thing in answering challenges in the business competition it is developing. To achieve this determine the Key Performance Indicator (KPI), the Rejected Rate and On-Time Delivery (OTD) to measure the extent of the performance that has been achieved and how to develop it, shape the work culture of Kaizen which commits to continuous improvement and value chain analysis largely determine the process of developing production and service quality. The Kaizen culture and value chain applied in achieving the KPI target in this study succeeded in reducing the KPI Rejected Rate by 0. 46% and raise OTD by 2. 22%. The method used in this study uses a review of literature studies, observations, and direct interviews of the plant manager of one of the largest optical lenses manufacturers in Indonesia using data comparisons in 2018 and 2020.